Bioakumulasi Logam Berat Timbal (Pb) dan Kadmium (Cd) pada Organ Timpakul Periopthalmodon schlosseri dan Boleopthalamus boddarti di Desa Kuala Tambangan - Holison Bendarani Sabatano; Hidayaturrahmah Hidayaturrahmah; Krisdianto Krisdianto (Bioscientiae, 2017)
Heavy metals found in water bodies will accumulate in sediments and bodies of aquatic biota both diffusion and through the food chain. This study was conducted to determine the bioaccumulation of heavy metals lead and cadmium in the organs of mudskipper P. schlosseri and B. boddarti, water, sediment, and small mangrove crabs as a food supplement. The collection was carried out in the Kuala Tambangan village by means of a purposive sample. The process of analysis of heavy metals is carried out on the gills, skin, liver, kidneys and embalmed meat. Surgical implants were analyzed using the ASS method. The first test results were the highest Pb metal 12.49 mg / kg and Cd 5.30 mg / kg in the kidney of P. schlosseri. The results of the analysis on the kidneys of B. boddarti species contained the highest Pb content of 7.56 mg / kg and Cd 3.94 mg / kg. The second test results of analysis of the content of heavy metals Pb and Cd in undetectable tympanic organs that is <0.24 mg / kg for all organs measured. The testing of the three Pb and Cd metal contents was partially undetectable, some containing heavy metals but still below the quality standard, except that the content of Cd in the liver of P. Schlosseri ie 0.364 mg / kg had exceeded the normal threshold. Pb metal content in tide water reaches 0.07 ml / l and passes the quality standard, while the Pb and Cd content in sediment and mangrove crabs as food chain is still below the standard and some heavy metals are not detected.